Prevalensi Konsumsi Kopi dan Hubungannya Dengan Tekanan Darad - Nur Melizza; Anggraini Dwi Kurnia; Nur Lailatul Masruroh; Yoyok Bekti Prasetyo; Faqih Ruhyanudin; Erma Wahyu Mashfufa; Fitria Kusumawati (Faletehan Health Journal, 2021)
Hypertension is known as the silent killer or deadly disease in secret because it has no specific signs and symptoms. Coffee consumption has historically been considered to have a negative effect on the body and is often linked as a factor that can lead to high blood pressure. The purpose of this study was to determine the relationship between coffee consumption and blood pressure in hypertensive patients. The design in this study used a cross-sectional study. Respondents of this study were 36, taken using a sampling technique, namely purposive sampling with inclusion criteria: consuming coffee and being willing to be respondents; and exclusion: had a history of other chronic diseases such as endocrine disorders. Data collection using a questionnaire and Spearman correlation statistical test. The results showed that there was a relationship between coffee consumption and blood pressure, respondents consumed the most coffee in the mild and moderate category with the majority of blood pressure being stage 1 hypertension. The results of the Spearman correlation test concluded that there was a relationship between coffee consumption and blood pressure in hypertensive patients. The correlation coefficient (r) of this study shows positive results, namely 0.424, which means that there is a strong enough relationship between coffee consumption and blood pressure. The increasing frequency of coffee will further increase the increase in blood pressure in hypertensive patients.